Aliran Al-Mujbirah dan Kesan Pemikirannya di Malaysia - Wan Ali, Wan Zailan Kamaruddin (Jurnal Usuluddin, 2000)
This article is an attempt to elaborate the development of al-Mujbirah as one of the earliest Muslim sects and also to analyse the influences and impacts of al-Jabariyyah in the Muslim world and in Malaysia.